2014
DOI: 10.4077/cjp.2014.bab178
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of NPC-14686-Induced [Ca^(2+)]i Rises and Non-Ca^(2+)-Triggered Cell Death in MG63 Human Osteosarcoma Cells

Abstract: NPC-14686 has been shown to have anti-inflammatory effect in previous studies, but the mechanisms are unclear. The effect of NPC-14686 on cytosolic Ca²⁺ concentrations ([Ca²⁺]i) and viability in MG63 human osteosarcoma cells was explored. The Ca²⁺-sensitive fluorescent dye fura-2 was applied to measure [Ca²⁺]i. NPC-14686 at concentrations of 100-500 μM induced a [Ca²⁺]i rise in a concentration-dependent manner. The response was reduced by 80% by removing Ca²⁺. NPC-14686 induced Mn²⁺ influx leading to quenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The [Ca 2+ ] i was measured as previously described (6,24,25). Confluent cells grown on 6 cm dishes were trypsinized and made into a suspension in culture medium at a concentration of 10 6 /ml.…”
Section: [Ca 2+ ] I Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The [Ca 2+ ] i was measured as previously described (6,24,25). Confluent cells grown on 6 cm dishes were trypsinized and made into a suspension in culture medium at a concentration of 10 6 /ml.…”
Section: [Ca 2+ ] I Measurementsmentioning
confidence: 99%
“…For calibration of [Ca 2+ ] i , after completion of the experiments, Triton X-100 (0.1%) and CaCl 2 (5 mM) were added to the cuvette to obtain the maximal fura-2 fluorescence (6,16,24,25). The Ca 2+ chelator EGTA (10 mM) was subsequently added to chelate Ca 2+ in the cuvette to obtain the minimal fura-2 fluorescence.…”
Section: [Ca 2+ ] I Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The [Ca 2+ ] i was measured as previously described. 13 15 Confluent cells grown on 6 cm dishes were trypsinized and suspended in medium at a concentration of 10 6 cells per milliliter. Cell viability was assayed by trypan blue exclusion (adding 0.2% trypan blue to 0.1 ml cell suspension).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 In order to explore the effect of amitriptyline on [Ca 2+ ] i in human osteosarcoma cells, the MG63 cell line was used because it induced significant [Ca 2+ ] i elevation when stimulated by many chemicals. It has been reported that in this cell line, [Ca 2+ ] i rises can be triggered in response to the addition of various chemicals such as NPC-14686, 13 sertraline, 14 and 3,3′-diindolylmethane. 15…”
Section: Introductionmentioning
confidence: 92%